Penyuluhan Pemanfaatan Lemak Kakao untuk Pembuatan Sabun Padat - Anggreni , Salcy; Wahyuni, Yuyun; Heliana, Almaria (LPPM Universitas Flores, 2023)
Cocoa butter is a by-product in the production process of chocolate bars and chocolate powder. In Bloro Village, Nita District, Sikka Regency, cocoa butter is produced in quite significant quantities, considering that Bloro Village is one of the largest cocoa producers in Sikka. The